CD109 regulates the inflammatory response and is required for the pathogenesis of rheumatoid arthritis. Issue 12 (27th August 2019) - Song, Guanhua; Feng, Tingting; Zhao, Ru; Lu, Qiqi; Diao, Yutao; Guo, Qingwei; Wang, Zhaoxia; Zhang, Yuang; Ge, Luna; Pan, Jihong; Wang, Lin; Han, Jinxiang
Abstract : Objective: The aim of this study was to investigate the role of CD109 in rheumatoid arthritis (RA) fibroblast-like synoviocytes (FLSs) and to evaluate its potential as a therapeutic target. Methods: CD109 expression was examined in synovial tissues and FLSs from RA patients and collagen-induced arthritis (CIA) model mice. CD109-deficient mice were developed to evaluate the severity of CIA. Small interfering RNAs and a neutralising antibody against CD109 (anti-CD109) were designed for functional or treatment studies in RA FLSs and CIA. Results: CD109 was found to be abundantly expressed in the synovial tissues from RA patients and CIA mice. CD109 expression in RA FLSs was upregulated by inflammatory stimuli, such as interleukin-1β and tumour necrosis factor-α. Silencing of CD109 or anti-CD109 treatment reduced proinflammatory factor production, cell migration, invasion, chemoattractive potential and osteoclast differentiation, thereby reducing the deleterious inflammatory response of RA FLSs in vitro. Mice lacking CD109 were protected against arthritis in the CIA model. Anti-CD109 treatment prevented the onset and ameliorated the severity of CIA lesions. Conclusion: Our study uncovers an antiarthritic role for CD109 and suggests that CD109 inhibition might serve as a promising novel therapeutic strategy for RA.